Peculiarities of Hybrid Learning - Hovhannisyan, Meri; Hovsepyan, Nune (History and Culture, 2025)
The objectives of the study are to clearly distinguish between the often erroneously identified concepts of "hybrid" and "blended learning" and to analyze the features of the hybrid learning. Our task is to discover the essence, the advantages and disadvantages of the hybrid learning, pedagogical problems that take place in the hybrid learning, as well as the ways of their solution. General scientific - logical methods, as well as private or special methods - methods of analysis and comparison – have been used during the comprehensive study of the problem put forward within the framework of the topic.As a result of the study we came to a conclusion that the hybrid learning is a synchronous format of education, a method of learning, combining the best sides of online education and individual education. The basic difference between the blended learning and the hybrid learning is that the hybrid learning is focused on an equal level of full-time and online education, meanwhile the blended learning supposes any unequal application of both types of learning, a variety of teaching methods. The opportunities provided by information technologies and limitations, imposed by the pandemic, force to seek some effective ways of the solution of branch problems, providing the systematic and qualitative learning of the generations grown up in the epoch of smartphones.
Keywords: the hybrid learning; the blended learning; the distance learning; the online learning; the method of learning; the full-time learning; the comtinuity of education; pandemic; information technologies